The Analytical Approach to Evaluate the Load-Displacement Relationship of Rock Bolts - Jianhang Chen; Shengli Yang; Hongbao Zhao; Junwen Zhang; Fulian He; Shuaifeng Yin (Advances in Civil Engineering)
Fully grouted rock bolts are widely used in civil engineering and mining engineering, playing a significant role in keeping the stability and safety of excavations. In this paper, the load transfer mechanism of fully grouted rock bolts was studied with an analytical model. A trilinear model was used to depict the bond-slip behaviour of the bolt/grout interface. The displacement of the confining medium was involved in this analytical model. Then, the shear stress propagation along the bolt/grout interface was analysed in the elastic, elastic-softening, elastic-softening-debonding, softening-debonding, and debonding stages. Experimental pull-out tests were used to validate this analytical model. There was a good correlation between experimental and analytical results. A parametric study was conducted to evaluate the influence of Young’s modulus of the confining medium, the shear strength of the bolt/grout interface, and the residual shear strength of the bolt/grout interface on the load transfer performance of rock bolts. The results show that increasing Young’s modulus of the confining medium was beneficial for improving the load transfer performance of rock bolts. However, once Young’s modulus of the confining medium was beyond a critical limit, it had marginal effect on the peak load of rock bolts. Furthermore, increasing the shear strength of the bolt/grout interface and the residual shear strength of the bolt/grout interface led to rising of the peak load of rock bolts. However, compared with the residual shear strength of the bolt/grout interface, increasing the shear strength of the bolt/grout interface had more apparent effect in improving the peak load of rock bolts.